PENGARUH MODEL PEMBELAJARAN TGT DENGAN CONCEPT ATTAINMENT BERBANTUAN FISHBOWL UNDIAN TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA - Mita Alfania Ahda; Desy Anindia Rosyida; Adin Fauzi (JS (JURNAL SEKOLAH), 2023)
Abstract: The low understanding of students' concepts in the field of mathematics is the background of this research. The purpose of this study was to describe student learning activities and to determine the effect of applying the TGT learning model with the fishbowl lottery-assisted attainment concept on the understanding of mathematical concepts in grade IV elementary school students. Quasi-experiment is a type of research that is used by applying a nonequivalent control group design. The research population was fourth grade students at SDN Kanigoro 3 with a total of 58 students with a sample of 45 students. During the two learning processes, the percentage of student activity obtained by the experimental class was 84.54% with good criteria, while the percentage of student activity in the control class was 76.19% with sufficient criteria. The results of the hypothesis test show that the tcount is 2.235 and 2.235, while the ttable value is 2.017. So, Tcount > ttable (2.235 > 2.0117 and 2.235 > 2.017), which means there is a difference in the mean score between the experimental class and the control class. Ho is rejected and Ha is accepted is the conclusion in this study.Keywords: TGT, Concept Attainment, Fishbowl Lottery, Concept Understanding. Abstrak: Rendahnya pemahaman konsep siswa dalam bidang studi matematika menjadi latar belakang penelitian ini. Adapun tujuan penelitian ini yaitu untuk mendeskripsikan aktivitas belajar siswa dan mengetahui pengaruh penerapan model pembelajaran TGT dengan concept attainment berbantuan fishbowl undian terhadap pemahaman konsep matematika siswa kelas IV sekolah dasar. Eksperimen semu merupakan jenis penelitian dalam riset ini serta menerapkan desain nonequivalent control group design. Populasi penelitian yaitu siswa kelas IV SDN Kanigoro 3 dengan jumlah 58 siswa dengan sampel 45 siswa. Selama dua kali proses pembelajaran, presentase aktivitsa siswa yang diperoleh kelas eksperimen yaitu 84,54% dengan kriteria baik, sedangkan untuk presentase aktivitas siswa kelas kontrol adalah 76,19% dengan kriteria cukup. Hasil uji hipotesis yaitu thitung 2,235 serta 2,235, Adapun nilai ttabel 2,017. Jadi, Thiung > ttabel (2,235 > 2,0117 dan 2,235 > 2,017), yang berarti skor rerata diantara kelas eksperimen serta kelas kontrol terjadi perbedaan. Ho ditolak dan Ha diterima merupakan kesimpulan dalam penelitian ini.Keywords: TGT, Concept Attainment, Fishbowl Undian, Pemahaman Konsep.